Informal Cross-Border Trade: Malaysia-Indonesia Borders The Conceptualisation From ‘Authority-Defined’ To "Everyday-Defined" - Fauzie Sarjono; Endang Rudiatin (BASKARA : Journal of Business and Entrepreneurship, 2022)
For these border studies, understanding borderlanders provides a new narrative about boundaries. The history of a nation-state of a collective nature, the alignment of power, economic segmentation, and integration of culture, ethnicity, and identity, religion, the behavior of marginal communities, as well as modern socio-political segregation are variables that can be raised in various disciplines. In this study, we offer a qualitative method with an ethnographic perspective, as many anthropologists do, but with a constructivist approach. We call it the conceptualization of "Authority-Defined" to "Everyday-Defined." The diversity of narratives and connotations in unraveling boundaries gives the perspective of contextual interpretation in different positions. Surely, understanding boundaries should also be seen in such a detailed context that the actors of border studies, i.e., society, are observed through the lens of meaning boundaries in their everyday lives. These differences lead to findings that are rich in dynamic and varied border backgrounds. This discussion focused on on-the-ground findings about informal cross-border trade, specifically at the Malaysia-Indonesia border. A trading system built by local communities is certainly different from the trade system in non-border areas and even in the country's capital area.